Production function implementation in an agent-based simulation. (2015) - Šperka, Roman; Spišák, Marek
The aim of the paper is to describe the seller-to-customer negotiation in the business processes (sales) of a virtual company. Based on it we propose an innovative approach to simulate, investigate and to predict some of the key performance indicators of a trading company. The methods used to implement the simulation framework in the form of multi-agent system come out of the agent-based modelling and simulation techniques. The framework should be a basic part of a management information system operating in the integration with real system of a company (e.g., ERP system). The paper firstly presents some of the existing theories about consumer behaviour and the types of factors influencing it. Secondly, it characterises multi-agent model of a virtual company, the agents participating in the seller-to-customer negotiation, and the production function. Finally, the simulation results and their validation are described. To conclude, the proposed approach with the use of seller-to-customer negotiation could properly contribute to better decision-making process of a company's management.